Using ultrasound to diagnose emergency states in acute heart failure - A. Koltunova; I. Beshlyga; V. Beshlyaga (Ukrainian Journal of Cardiovascular Surgery, 2018)
Echocardiographic study is recommended for the diagnosis and assessment of urgent states in patients with acute heart failure. The development of ultrasound technology has led to the introduction of this study not only in the practice of the cardiologist, but also anesthesiologist at the critical care units. The obtained results of echocardiographic examination improve the accuracy of early diagnosis, tactics and monitoring the results of the proposed treatment in patients with acute heart failure. The use of goal-directed echocardiography by intensive care physicians for the treatment of acute heart failure strengthens the traditional model of medical care.